ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA PEGAWAI DI KANTOR KECAMATAN TEMBALANG KOTA SEMARANG - Nurmiyanti Wulandari; Moch Mustam (Journal of Public Policy and Management Review, 2016)
The problem in this research is less than optimal performance of employees at the District Office Tembalang Semarang . The purpose of this study was to determine how the employee's performance and the factors that affect the performance of employees at the District Office Tembalang Semarang . This research use a research design with a quantitative approach . The results of this study indicate that there is a relationship positive influence on the ability to work with corelation coefficient (r = 0.778; KD = 39.94%), interests of employees (r = 0.332; KD = 11.02%), leadership (r = 0.552; KD = 27.24%), organizational climate (r = 0.433; KD=18,74%), motivation (r = 0.315; KD = 9.92%) and job satisfaction (r = 0.344; KD = 11.83%). It means if capability more high, the corresponding interests, the better the behavior of its leadership, the more conducive organizational climate, motivation is getting high and job satisfaction is getting high, it make the performance of employees more high than before. Because the factors that affect performance are the abilities, interests of employees, leadership, organizational climate, motivation and job satisfaction then, to improve employee performance can be done by improving the ability, to adjust interest in his work, improve the behavior of the leadership, making organizational climate conducive increase maintaining employee motivation and satisfaction as well as providing functional training to employees and PIM training on leadership, since there are a lot of employees who do not follow the training.